Modelo didáctico “I.D.C.”, basado en la teoría de las seis lecturas para estimular la decodificación primaria de las niñas del 2º grado de educación primaria de la I.E. Nº 80397 “Hermanos Albújar y Manuel Guarniz” Guadalupe, 2010 - Vértiz Quiroz, Cindy Rosmery (2011)
The present work of investigation titled: " Didactic Model " I.D.C. "; based on the theory of six readings, to stimulate the primary decodificacion of the girls of 2 º degree of primary of the I. E. N º 80397 " Brothers Albújar and Manuel Guarniz " Guadalupe - 2010 ", it had as aim determine the level of decodificación primary across the application of the didactic model " I.D.C. ", based on the theory of six readings in the girls of 2 ° degree of primary of the I.E.N ° 80397 " Brothers Albújar And Manuel Guarniz " of Guadalupe's district. The Type of used investigation is applied or technological, with quasiexperimental design, with group control and experimentally with pretest and postest; the same one that carried out with a sample of 61 pupils of 2 º degree, 31 girls of the experimental group and 30 girls of the group control of the sections To and B respectively, to both groups applied the pre to them and postest. The results demonstrate that the didactic model " I.D.C. " based on the theory of six readings it has increased significantly in the experimental group the areas of Lexicon, Synonymy and Contextualizacion and in a minimal way in Radicacion, for what one affirms that the didactic model " I.C.D. " It has had positive effects. We hope that the results obtained in the present investigation use as contribution the teachers involved in the education of the children and this way by means of these pedagogic limits the educational practice is improved.